CyTOF Analysis Reveals a Distinct Immunosuppressive Microenvironment in IDH Mutant Anaplastic Gliomas - Fu, Weilun; Wang, Wenjing; Li, Hao; Jiao, Yuming; Weng, Jiancong; Huo, Ran; Yan, Zihan; Wang, Jie; Xu, Hongyuan; Wang, Shuo; Wang, Jiangfei; Chen, Dexi; et al. (Frontiers in Oncology, 2021)
The immune microenvironment is important for the development, progression, and prognosis of anaplastic glioma (AG). This complex milieu has not been fully elucidated, and a high-dimensional analysis is urgently required. Utilizing mass cytometry (CyTOF), we performed an analysis of immune cells from 5 patients with anaplastic astrocytoma, IDH-mutant (AAmut) and 10 patients with anaplastic oligodendroglioma, IDH-mutant and 1p/19q codeletion (AOD) and their paired peripheral blood mononuclear cells (PBMCs). Based on a panel of 33 biomarkers, we demonstrated the tumor-driven immune changes in the AG immune microenvironment. Our study confirmed that mononuclear phagocytes and T cells are the most abundant immunocytes in the AG immune microenvironment. Glioma-associated microglia/macrophages in both AAmut and AOD samples showed highly immunosuppressive characteristics. Compared to those in the PBMCs, the ratios of immune checkpoint-positive exhausted CD4+ T cells and CD8+ T cells were higher at the AG tumor sites. The AAmut immune milieu exhibits more immunosuppressive characteristics than that in AOD.